About the System of Procedural Guarantees to Ensure the Rights of Participants in Criminal Proceedings - Bazarova, Dildora (International Journal of Psychosocial Rehabilitation, 2020)
At present, one of the most pressing problems in Uzbekistan is as follows and in the majority of states on the way of democratization of public life, where the main value is the human being, the provision of reliable and effective guarantees of rights and freedoms of the individual, its protection, especially in the sphere of criminal proceedings, running in the atmosphere of high tension and negative emotional and psychological load for the majority of participants of criminal proceedings, remains. It cannot be argued that the problems of ensuring and implementing human rights guarantees, including the process of its participation in criminal proceedings, have previously not attracted the attention of legal scholars or have been insufficiently researched in depth and comprehensively